AN EXPERIMENTAL STUDY OF WATER AND CARBON DIOXIDE SOLUBILITIES IN MID-OCEAN RIDGE BASALTIC LIQUIDS. PART II: APPLICATIONS TO DEGASSING - Dixon J.E.; Stolper E.M. (My University, 1995)
Degassing processes in basaltic magmas rich in both water and carbon dioxide can be modeled using the solubilities of the endmember systems and the assumption of Henry's law. Suites of vapor-saturated basaltic melts having a range of initial CO_2/H_2O ratios and erupted over a narrow depth interval will define negatively sloped arrays on an H_2O vs CO_2 plot. It is important that all of the major volatile species be considered simultaneously when interpreting trends in dissolved volatile species concentrations in magmas. Based on measured concentrations of water and carbon dioxide in basaltic glasses, the composition of the vapor phase at 1200°C that could coexist with a basaltic melt and the pressure at which it would be vapor saturated can be calculated. The range in vapor compositions in equilibrium with submarine basalts reflects the range in water contents in the melts characteristic of each environment. The ranges in the molar proportion of CO_2 in vapor phases (X^ν_(CO2)) calculated to be in equilibrium with submarine tholeiitic glasses are 0⋅93–1⋅00 for mid-ocean ridge basalts (MORB), 0⋅60–0⋅99 for glasses from Kilauea [representative of ocean island basalts (OIB)] and 0–0⋅94 for glasses from back-arc basins (BABB). MORB glasses from spreading centers ranging from slow (e.g. the Mid-Atlantic Ridge) to fast (e.g. East Pacific Rise, 9–13°N) are commonly supersaturated with respect to CO_2-rich vapor, resulting from magma ascent rates so rapid that magmas erupt on the sea-floor without having been fully degassed by bubble nucleation and growth during ascent. In contrast to the MORB glasses, volatile contents in submarine glasses from Kilauea are consistent with having been in equilibrium with a vapor phase containing 60–100 mol% CO_2 at the pressure of eruption, reflecting differences in average magma transport rates during eruptions at mid-ocean ridges and hotspot volcanoes. Degassing during decompression of tholeiitic basaltic magma is characterized by strong partitioning of CO_2 into the vapor phase. During open system degassing, CO_2 is rapidly removed from the melt with negligible loss of water, until a pressure is reached at which the melt is in equilibrium with nearly pure water vapor. From this pressure downward, the water content of the melt follows the water solubility curve. During closed system degassing, water and CO_2 contents in vapor-saturated basaltic magmas will depend strongly on the vapor composition as determined by the initial volatile concentrations. Deviation from open system behavior, toward lower dissolved H_2O and CO_2 saturation concentrations at a given pressure, will be greatest in melts having high total volatile concentrations and high CO_2:H_2O ratios. Closed system degassing of basaltic melts having the low initial H_2O and CO_2 contents typical of MORB and OIB, however, are similar to the open system case.